Strengthening 3rd Graders' Essay Writing: Contextual Teaching for Lasting Skills: Meningkatkan Kemampuan Menulis Esai Murid Kelas Tiga Melalui Pembelajaran Kontekstual - Anis Yusandita; Vevy Liansari (Academia Open, 2023)
This study aimed to investigate the effect of Contextual Teaching and Learning (CTL) on the development of simple essay writing skills in third grade students. A quantitative pre-experimental design with a one-group pretest-posttest approach was employed. The participants consisted of 23 students from Elementary School Plus Cahaya Budaya, selected using saturated sampling. The data were collected through pretest and posttest essay questions, and the analysis was conducted using t-test. The results indicated a significant improvement in students' writing skills after implementing the CTL learning model, as evidenced by a one-tailed p-value of 0.000 (p < 0.05). This suggests that the CTL approach positively influences the development of simple essay writing skills in third grade students. The implications of these findings underscore the importance of implementing effective teaching strategies, such as CTL, to enhance students' writing abilities at an early stage. Highlights: CTL significantly improves simple essay writing skills in third grade students. Quantitative research reveals the positive impact of CTL on writing abilities. Pre-experimental design provides insights into the effectiveness of CTL in elementary education. Keywords: Contextual Teaching and Learning, simple essay writing skills, third grade students, quantitative research, pre-experimental design.